Quale comunità per quale territorio - Sergio De La Pierre (Scienze del Territorio, 2020)
A wide-ranging reflection on the theme of ‘community’ is all the more urgent today, because this word is inflated and at the same time necessary for a perspective of ‘regeneration’ of society. The industrial era tended to marginalise the historical forms of ‘community’ organisation, but then slipped into a vision of both man and world centred on individual competitiveness and purely economic values. This is why today we are witnessing the rebirth of a strong ‘need for community’: this, even if often manifests itself as a defensive closure to the world (the ‘communities of resentment’), actually can allude to new paths of civilization, provided that the principles of individual freedom and a participatory community democracy, based on the idea of multidimensional integration, are safeguarded.